Electrocardiogram changes and wall motion abnormalities in the acute phase of Tako-Tsubo syndrome. Issue 6 (October 2016) - Weihs, Valerie; Szücs, Daniela; Fellner, Barbara; Eber, Bernd; Weihs, Wolfgang; Lambert, Thomas; Metzler, Bernhard; Titscher, Georg; Hochmayer, Beate; Dechant, Cornelia; Eder, Veronika; Siostrzonek, Peter; et al.
Background: The Tako-Tsubo syndrome is still rarely diagnosed in patients presenting with symptoms of acute myocardial ischaemia. It is accompanied by wall motion abnormalities of the left ventricle but significant narrowings or occlusions of epicardial coronary arteries are absent. We investigated a potential relationship between electrocardiogram (ECG) changes, wall motion abnormalities and gender influence of Tako-Tsubo syndrome in an Austrian cohort of Tako-Tsubo syndrome patients. Methods and results: We were recently able to describe four different anatomical types of Tako-Tsubo syndrome in 153 patients of the Austrian Tako-Tsubo syndrome registry. In the present retrospective analysis we investigated ischaemia-related changes in the first diagnostic ECG for the different types of Tako-Tsubo syndrome: the apical and the combined apical-midventricular type showed most frequently a ST elevation (41.1% and 35.3%), whereas the midventricular type of Tako-Tsubo syndrome was more often accompanied by T wave inversion (60%). ECG changes in relation to the Tako-Tsubo syndrome type were similar in women and men. There was no difference in the prevalence of clinical complications among patients presenting with ST elevation or left bundle branch block (14.5%) compared with patients without ST elevation (10.4%) ( p =0.476). Conclusion: Patients with Tako-Tsubo syndrome show characteristic ECG changes in the first diagnostic ECG which are associated to some extent with the anatomical type of Tako-Tsubo syndrome, but these ECG changes were not related to clinical outcome.